Bioavailability of soil phosphorus forms in notillage system Biodisponibilidade de formas de fósforo acumuladas em solo sob sistema plantio direto - Gatiboni L.C.* (2007)
The addition of fertilizers to the soil increases P contents in many forms of different bond energies with soil colloids. This has been observed in the soil surface layer under no tillage system, however there is little information about the availability of these P forms to plants. The study aimed to evaluate the bioavailability of P forms of a soil under no tillage with P applications. Samples were collected (0-10 cm) in a Rhodic Hapludox that had been fertilized with 0,180, 360, 540, and 720 kg ha-1 Of P2O5 over six years of cultivation prior to this study. The samples were dried, ground, Med in 2 kg pots and subjected to 15 successive crops without replacement of absorbed P. After every three successive crops, soil samples were collected for analysis. Phosphorus fractionation was analyzed by Hedley's method. Results showed that inorganic P extracted by NaHCO30.5 mol L-1 has a buffering capacity similar to P available by anion exchange resin, and can be considered labile P as well. In the long term, all soil P forms act in the soil solution buffer. In fertilized soils, the inorganic and organic P forms act in a similar way buffering the absorbed P by plants. In soils with little or no fertilization, the organic forms are the main P source of plants.